2004
DOI: 10.1167/iovs.03-1050
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas Keratitis: Protease IV Gene Conservation, Distribution, and Production Relative to Virulence and OtherPseudomonasProteases

Abstract: The protease IV gene and its product are common to P. aeruginosa, but not to other Pseudomonas species. Protease IV activity varies among P. aeruginosa strains, and a mutant specifically deficient in this activity produced alkaline protease and had reduced corneal virulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…However, the ability to withstand surfactant and stability in solvent medium is a lesser-known quality of these enzymes. P. aeruginosa has been reported to produce at least four different types of endopeptidases [Kessler et al 1998;Traidej et al, 2003]: (i) elastase or pseudolysin (LasB) -a 33-kDa zinc metallopeptidase [Kessler and Ohman, 2004a;Ogino et al, 2000], (ii) staphylolysin or LasA endopeptidase -a 20-kDa zinc metalloendopeptidase [Kessler et al, 1998;Kessler and Ohman, 2004b], (iii) alkaline protease or aeruginolysin -a 50-kDa zinc metalloendopeptidase [Morihara and Homma, 1985;Okuda et al, 1990;Wallach, 2004] and (iv) protease IV or lysyl endopeptidase -a 26-kDa serine protease encoded by protease IV gene [Caballero et al, 2004;Engel et al, 1998]. Of these, the alkaline protease and elastase (both metalloproteases) have been reported to be the most abundant ones [Parmely, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…However, the ability to withstand surfactant and stability in solvent medium is a lesser-known quality of these enzymes. P. aeruginosa has been reported to produce at least four different types of endopeptidases [Kessler et al 1998;Traidej et al, 2003]: (i) elastase or pseudolysin (LasB) -a 33-kDa zinc metallopeptidase [Kessler and Ohman, 2004a;Ogino et al, 2000], (ii) staphylolysin or LasA endopeptidase -a 20-kDa zinc metalloendopeptidase [Kessler et al, 1998;Kessler and Ohman, 2004b], (iii) alkaline protease or aeruginolysin -a 50-kDa zinc metalloendopeptidase [Morihara and Homma, 1985;Okuda et al, 1990;Wallach, 2004] and (iv) protease IV or lysyl endopeptidase -a 26-kDa serine protease encoded by protease IV gene [Caballero et al, 2004;Engel et al, 1998]. Of these, the alkaline protease and elastase (both metalloproteases) have been reported to be the most abundant ones [Parmely, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…13 However, Caballero et al have demonstrated that significant alkaline protease activity can be produced by this strain. 12 Similarly, Marquart et al have shown that P. aeruginosa can modulate the expression of protease in response to environmental levels of magnesium and/or calcium. 56 Additionally, Marquart et al have recently discovered an additional protease that was not formerly recognized as a product of P. aeruginosa.…”
Section: Discussionmentioning
confidence: 97%
“…29,31,35 Unfortunately, these protease-deficient mutants retained their ability to produce protease IV, a known corneal virulence factor. 12,13 Thus, the loss of elastase B or alkaline protease could have been compensated for, in terms of ocular virulence, by the continued production of other proteases (e.g., protease IV).…”
Section: Discussionmentioning
confidence: 99%
“…To understand the mechanism of pathogenesis in keratitis caused by P. aeruginosa, the virulence factors as well as extracellular products, including proteases, [6][7][8] exotoxin A, 9 and biofilms, 10 have been investigated. Of these factors, proteases, including metalloproteases such as alkaline protease, elastase A, and elastase B, 11 are important in virulence.…”
mentioning
confidence: 99%